PENAMBAHAN PEKTIN DALAM PEMBUATAN SELAI LEMBARAN BUAH PEDADA (Sonneratia caseolaris). - Dorlan Simamora; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aimed was to obtain the combination of best of treatment the addition of pectin given to making fruit leather. This research was carried experienmentally using completely design randomized (CDR) with four treatment and four replications: P1 (Addition of pectin 1%), P2 (Addition of pectin 0.75%), P3 (Addition of pectin 0.5%), P4 (Addition of pectin 0.25%). Data obtained were treated by the Analisys of Varience (ANOVA) to allowed by Duncan New Multiple Range Test (DNMRT) the level 5%. The result showed that theaddition of pectin in making jam significantly sheets against the water content, content of ashes, content of coarse fiber, content total dissolved solids, degree acidity, content sucrose, hedonic test (color, scent, taste, of sweetness, plasticity and the overall assessment), descriptive test (colour, plasticity) and not significantly descriptive (the scent, taste and sweetness). P1 (pectin 0.25%) jam on sheets produce good. This jam 3.15 having a PH, in hedonic favored by the panelist and in descriptive bible brownish yellow, flavorful pedada, of a sweetish taste, not sweet of sweetness, plasticity springy and the overall assessment. The best treatment is P1 (addition of pectin 0,25%). Key words : Fruit Pedada, pectin and fruit leather